The Effect of Using the MARBEL Indonesian Culture Educational Game in Flipped Classroom Learning on the Science and Science Learning Outcomes - Rifqi Ainun Najib; Farid Ahmadi (Postgraduate, University of Mataram, 2025)
The purpose of this study is to ascertain how the Marbel Indonesian Culture Educational Game, when used in a flipped classroom, affects the scientific learning outcomes and science curriculum of fourth-grade students at SDN Kajen. This study employs quasi-experimental quantitative methodologies. Thirty-two grade 4 respondents from SDN Kajen participated in this study. Both test and non-test methods are used in data collection. The findings of this study demonstrate that student learning outcomes are impacted when the Indonesian Cultural Marbel educational game is used in Flipped Classroom instruction. The significance values for pair 1 (0.001 < 0.05) and pair 2 (0.001 < 0.005) demonstrate this. Additionally, the use of the instructional game Indonesian Cultural Marbel in Flipped Classroom Learning improves student learning results by 41.5%. The Marbel Budaya Indonesia educational game is therefore considered less effective in boosting the efficacy of Flipped Classroom learning because its N-Gain value of 0.415 places it in the less effective group.